Plan de negocios para la implantación de un restaurante turístico en Pujilí-Cotopaxi - Quishpe Quitiguña, Rosa Catherine (2011)
Micuna Ruphay will be an operation that will express, from its design and products a close relationship with Nature, the comfort and feeling of the Ecuadorian highlands. The business will be oriented to offer a quality gastronomic service to comply with food requirements of families coming from Quito, Latacunga and Ambato, people that are looking for the right place where they can enjoy typical Ecuadorian dishes in Pujilí-Cotopaxi. Persons who are anxious of being in harmony with nature and demand relax and recreation. The added value of the business will be a personalized service, providing clients the appropriate space and privacy. To the creative presentation of dishes, the restaurant will add areas of entertainment for children and handicrafts spaces. Many macro-economic and social factors favor the operation and success of the restaurant, which will provide impulse to the touristic industry in the area; however, there are external economic forces that represent a risk for the company, like the political instability and the increase of prices, among others. Reviewing the micro environment, we have been able to identify threats like the appearance of new competitors, but also opportunities for a better service, like the improvement of the road infrastructure, that will favor the business. The market study undertaken through personal polls with adult people in the cities of Quito, Ambato and Latacunga, the interviews with experts that operate big restaurant chains, the criteria of experts in the industry and successful family businesses operators, were complemented with information obtained in focal groups, all of which provided a positive business environment, the acceptance of the location and the dishes to be offered by the restaurant. To start activities the company will require an initial investment of US $. 143,336.49 American dollars that will be financed with personal funds and bank loans. Micuna Ruphay will be an operation that will express, from its design and products a close relationship with Nature, the comfort and feeling of the Ecuadorian highlands. The business will be oriented to offer a quality gastronomic service to comply with food requirements of families coming from Quito, Latacunga and Ambato, people that are looking for the right place where they can enjoy typical Ecuadorian dishes in Pujilí-Cotopaxi. Persons who are anxious of being in harmony with nature and demand relax and recreation. The added value of the business will be a personalized service, providing clients the appropriate space and privacy. To the creative presentation of dishes, the restaurant will add areas of entertainment for children and handicrafts spaces. Many macro-economic and social factors favor the operation and success of the restaurant, which will provide impulse to the touristic industry in the area; however, there are external economic forces that represent a risk for the company, like the political instability and the increase of prices, among others. Reviewing the micro environment, we have been able to identify threats like the appearance of new competitors, but also opportunities for a better service, like the improvement of the road infrastructure, that will favor the business. The market study undertaken through personal polls with adult people in the cities of Quito, Ambato and Latacunga, the interviews with experts that operate big restaurant chains, the criteria of experts in the industry and successful family businesses operators, were complemented with information obtained in focal groups, all of which provided a positive business environment, the acceptance of the location and the dishes to be offered by the restaurant. To start activities the company will require an initial investment of US $. 143,336.49 American dollars that will be financed with personal funds and bank loans. There are three economic scenarios for the cash flow that will support a five years period, where the evaluated financial indicators show positive rates of return for the investors as well as attractive net present value.There are three economic scenarios for the cash flow that will support a five years period, where the evaluated financial indicators show positive rates of return for the investors as well as attractive net present value.